2019
DOI: 10.1016/j.sjbs.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic and hydrothermal carbonization of date palm leaflets: Characteristics and ecotoxicological effects on seed germination of lettuce

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
3
16
1
Order By: Relevance
“…The shoot length was significantly reduced by the addition of biochar produced from peanut hull at 500 • C [38]. Contrarily, it was reported that biochar derived from date palm leaflets promoted the shoot length of lettuce [61]. However, the germination test in the previous study was carried out on filter papers, which could lead to the different outcomes compared to the germination test on biochar-sand mixtures in our study.…”
Section: Effects Of Corncob Biochar On Shoot Fresh Weightcontrasting
confidence: 55%
See 1 more Smart Citation
“…The shoot length was significantly reduced by the addition of biochar produced from peanut hull at 500 • C [38]. Contrarily, it was reported that biochar derived from date palm leaflets promoted the shoot length of lettuce [61]. However, the germination test in the previous study was carried out on filter papers, which could lead to the different outcomes compared to the germination test on biochar-sand mixtures in our study.…”
Section: Effects Of Corncob Biochar On Shoot Fresh Weightcontrasting
confidence: 55%
“…Based on the results of this study, corncob biochar could be used at a low application rate (10 t/ha) without a significant phytotoxic effect on seed germination. In a previous study, it was reported that biochar from date palm leaflets did not result in toxic effect on lettuce germination [61]. It was reported that the addition of biochar at low application rates (10-50 t/ha) increased germination of wheat [60].…”
Section: Effects Of Corncob Biochar On Shoot Lengthmentioning
confidence: 94%
“…Typically, the presence of glucose in lignocellulosic biomass inhibits nitrogen transfer to the bio-crude oil and aqueous phases (Qiu et al, 2019). Char with high nitrogen content used as an organic fertilizer can increase the amount of available nitrogen and phosphorous, increase crop yields, and reduce greenhouse gas emissions (Al-Wabel et al, 2018;Islam et al, 2021). Adjuik et al (2020) showed that CO 2 fluxes were 34% lower in HTL-char treated soils than in the control treatment.…”
Section: Carbon and Nitrogen Recovery Within Htl Productsmentioning
confidence: 99%
“…These organic pollutants in P-BC-LDHs may be considered one of the factors inhibiting the growth of lettuce seedlings. It was reported that PAH-induced responses in several plants included the reduction of seed germination, hindered seedling development, and decreased root elongation due to the variable consequences of interference with cell wall modification and expansion, membrane permeability, and photosynthesis [36][37][38][39]. Therefore, to avoid any potentially toxic effects, the quantitative analyses of metal elements and PAHs, as well as pretreatment of P-BC-LDHs, should be performed prior to application for seed germination.…”
Section: Seed Germinationmentioning
confidence: 99%